2018
DOI: 10.1016/j.anifeedsci.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ruminal fermentation and microbial population of feedlot Nellore cattle fed crude glycerin and virginiamycin

Abstract: The objective of this experiment was to evaluate the effects of crude glycerin (CG) and virginiamycin (VM) diets on ruminal fermentation and microbial population of feedlot Nellore cattle. Eight rumen fistulated bulls (BW = 600 ± 34 kg; 26 ± 3 months) were used in a replicated 4 × 4 Latin square (21-d periods) with 2 × 2 factorial arrangement of treatments: diets without virginiamycin (VM−) or virginiamycin at 25 mg/kg DM (VM+) combined with diets without crude glycerin (CG−) or CG (80% glycerol) at 100 g/kg D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…M. elsdenii also produces propionate. In other studies, the abundance of Megasphaera elsdenii doubled after the use of crude glycerol (80% glycerol), but without a noticeable effect on rumen protozoa [ 40 ]. The presented changes in the rumen fluid microbiome explain the most frequently observed dynamics and directions of volatile fatty acid (VFA) changes.…”
Section: Effect Of Glycerol On Rumen Processes and Metabolismmentioning
confidence: 99%
“…M. elsdenii also produces propionate. In other studies, the abundance of Megasphaera elsdenii doubled after the use of crude glycerol (80% glycerol), but without a noticeable effect on rumen protozoa [ 40 ]. The presented changes in the rumen fluid microbiome explain the most frequently observed dynamics and directions of volatile fatty acid (VFA) changes.…”
Section: Effect Of Glycerol On Rumen Processes and Metabolismmentioning
confidence: 99%
“…Increased feed intake with glycerol suggests improved energy utilization efficiency by ruminal microbiota (Andrade et al., 2018). Moreover, the physical characteristics of glycerol, such as viscosity, could maintain feed particles aggregate and reduce ruminal fill (Castagnino et al., 2018). Recently, Bajramaj et al.…”
Section: Application Of Glycerol In the Dairy Animal Industrymentioning
confidence: 99%
“…Fernando et al [33] indicated that an increase in Selenomonas ruminantium populations together with other species such as Megasphaera elsdenii could decrease the amount of lactic acid in high-concentrate diets, since these microorganisms are considered lactate-using species. Castagnino et al [9] noted, despite not finding an increase in the population of Selenomonas ruminantium , that when adding 10% glycerin to the diets of beef cattle, there was an increase in Megasphaera elsdenii ; furthermore, they did not find changes in other populations such as fibrolytic bacteria ( Ruminococcus albus and Fibrobacter succinogenes ).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, no differences were found on the effective degradability for two very different fibrous raw materials (barley straw and sugar beet pulp), when glycerin was increased. In addition, Castagnino et al [9] reported that high-concentrate diets with 10% glycerin that were fed to beef cattle did not affect the apparent digestibility of DM or NDF, nor the abundance of fibrolityc bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation